Historical Views of Spiritism and Mediumship in Spain, 1880-1930: Ciencia y Espiritismo en Espana by Andrea Graus - Alvarado, Carlos S. (Journal of Scientific Exploration, 2021)
Little is known by non-Spanish speakers about the history of Spiritism and psychical research in Spain. Standard English-language sources such as Frank Podmore’s Modern Spiritualism (1902) and Arthur Conan Doyle’s The History of Spiritualism (1926) do not cover developments in that country.1 There is a useful historical outline of the topic in philosopher and educator Mario Méndez Bejarano’s Historia de la Filosofía en España Hasta el Siglo XX (n.d., Chapter 17, Part 14). Much of relevance can be found in the new historiography about the subject in Spain which, like that in some other countries, has grown in recent decades.2 Other recent studies have included psychical research as well. Particularly useful are the essays compiled by Annette Mülberger (2016) in Los Límites de la Ciencia: Espiritismo, Hipnotismo y el Estudio de los Fenómenos Paranormales (1850–1930), and articles about such topics as the attitudes and approaches of specific investigators (Vilaplana Traviera & Mülberger, 2003), turning tables (González de Pablo, 2006), and prominent clairvoyance studies (Mülberger & Balltondre, 2013). Andrea Graus, the author of the book reviewed here, has also made various significant contributions. Graus, a historian at the Centre Alexandre Koyré, has published various articles about mediumistic investigations, and the ideas of Spanish physicians (e.g., Graus, 2015, 2016). This work has been expanded in the book reviewed here, Ciencia y Espiritismo en España, 1880–1930 (see Figure 1).